2006
DOI: 10.3892/or.15.4.797
|View full text |Cite
|
Sign up to set email alerts
|

Disordered expression of HOX genes in human non-small cell lung cancer

Abstract: We hypothesized that the disordered tissue architecture in cancer results from the steps that the cells execute the program designed during ontogeny in a spatiotemporally inappropriate manner. HOX genes are known as master regulators of embryonic morphogenesis, and encode transcription factors which regulate the transcription of the downstream genes to realize the program of body plan. In this study, we quantified the expression levels of 39 HOX genes in 41 human non-small cell lung cancer (non-SCLC) and non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 12 publications
4
73
0
2
Order By: Relevance
“…Additionally, the knockdown of HOXA1 inhibited growth of cells and induced G1 arrest. These results demonstrate that, similar to previous studies, HOXA1 plays a role as a proto-oncogene in NSCLC cells (Abe et al, 2006;Cho et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the knockdown of HOXA1 inhibited growth of cells and induced G1 arrest. These results demonstrate that, similar to previous studies, HOXA1 plays a role as a proto-oncogene in NSCLC cells (Abe et al, 2006;Cho et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that HOXA1 is overexpressed in various cancers, including breast, liver, oral and lung cancer (Chariot et al, 1996;Abe et al, 2006;Bitu et al, 2012;Zha et al, 2012). The forced expression of HOXA1 promoted oncogenic transformation by modulating the p44/42 MAP kinase pathway and bcl-2 in MCF-10 cells (Mohankumar et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Here we have shown that disrupting the interaction between HOX and PBX proteins is sufficient to cause apoptosis in the NSCLC-derived cell lines, A549 and H23. Although earlier studies have also shown HOX genes to be dysregulated in NSCLC (Abe et al, 2006), to our knowledge this is the first report to describe these changes in a comprehensive manner allowing a direct comparison between expression in normal lung tissue, primary tumours and derived cell lines. This reveals that there is a large increase in transcription in most HOX genes of the HOXC and HOXD families when comparing normal lung tumour with primary tumours, and furthermore, this change is also present in A549 and H23, indicating that there has been a stable change in the transcriptome.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies, focusing on small groups of HOX genes, have shown that some are upregulated in lung cancer (Abe et al, 2006), but the functional significance of this is unknown. Here we present a comprehensive analysis of HOX expression in non-small-cell lung cancer (NSCLC) that reveals that many of the HOX genes have strongly elevated expression in malignant cells.…”
mentioning
confidence: 99%
“…The short arm of chromosome 7 is implicated as being involved in the initiation and/or progression of ADC and has been suggested to include critical cancer related genes in ADC (16)(17)(18). Job et al (15) demonstrated that the high frequency of copy number gains on chromosome 7p contained CARD11, ETV1 and IKZF1 genes in 78-92% of the ADCs observed.…”
Section: Discussionmentioning
confidence: 99%